Just because you're powerless doesn't mean they aren't out to get you: Low power, paranoia, and aggression - Schaerer, Michael (Institutional Knowledge at Singapore Management University, 2021)
Due to its pervasive negative consequences, failing to understand the origins of paranoia can be costly for organizations. Prior research suggests that powerful employees are particularly likely to experience paranoia as others want to exploit the resources they control, implying that employees low in power should feel less paranoid. In contrast, we build on Conservation of Resources Theory and sociocultural perspectives of power to argue that the inherent vulnerability associated with being low power also evokes paranoia as a protection mechanism. Because paranoia causes employees to form malevolent attributions towards others, we predict that paranoia, in turn, leads to aggressive tendencies. Five studies (N = 2,341), including three experiments, a correlational study, and an experience sampling study, support our predictions. We further find that the effect of low power on paranoia is weaker when employees can rely on other valuable resources, including individual (socioeconomic status) and social (organizational support) resources.